Reference values of amino acids and of common clinical chemistry in plasma of healthy infants aged 1 and 4 months. Issue 1 (31st July 2015) - Haschke‐Becher, Elisabeth; Kainz, Alexander; Bachmann, Claude
Abstract: Objective: To compare plasma levels of amino acids and clinical chemistry parameters in healthy infants at 1 and 4 months of age and to establish corresponding reference limits. Methods: Data of three multicenter studies assessing the safety of new infant formulas were used. During these studies infants of both age‐groups were either breast‐fed or received formulas of low or high protein content. All samples were analyzed centrally in the same accredited laboratory. Results: Plasma was collected from 521 infants in total, 157 boys and 135 girls aged 1 month and 121 boys and 108 girls aged 4 months. At the age of 1 month, 62 infants had received exclusively breast milk, 198 exclusively formula, and 27 both; in the 4‐months age group corresponding numbers were 49, 158 and 18, respectively; for 9 infants, diet was unknown. Concentrations of most amino acids and clinical chemistry parameters differed significantly between both ages. Regardless of age, most plasma amino acid levels were comparable or lower in breast‐fed than in formula‐fed infants whereas at 1 month of age most clinical chemistry parameters were higher. While in breast‐fed infants the plasma urea concentration decreased over 4 months of age, it increased in formula‐fed infants. There were significant differences between infants fed a low and high protein formula. At both ages, high protein formulas resulted in significantly higher threonine, 2‐aminobutyrate, and urea concentrations. Conclusions: For clinical use, age‐ and diet specific reference limits in infants are warranted.